Interoceptive Exposure for Reducing Anxiety in the Treatment of Panic Disorder - Ávila, Andressa Celente; Andretta, Ilana (Revista de Psicologia da IMED, 2014)
Panic disorder (PD) causes psychological and functional impairment in the individual's life. The interoceptive exposure (IE) is essential in the treatment of PD since it is aimed at reducing anxiety symptoms of a panic attack (PA), promoting habituation. Therefore, this study aimed to analyze the applicability of EI in reducing anxiety experienced in an AP induced through exercises that cause similar sensations. The study included three patients with a diagnosis of PD and agoraphobia, attending a school service. In three sessions of the EI were evaluated the level of intensity, similarity and anxiety with exercise, punctuated by patients on a scale of 0 to 10. The EI obtained positive results in treating patients, since there was a decrease in anxiety levels in the three patients and there was also correspondence between the level of intensity, similarity and anxiety, in which exercises were classified with the same level.